2023
DOI: 10.1177/15910199231157924
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy versus medical management for acute basilar artery occlusions: A meta-analysis of randomized trials

Abstract: Background Basilar artery occlusion (BAO) stroke is a catastrophic clinical event that results in significant morbidity and mortality. Whether MT is superior in improving outcomes remains largely inconclusive. We performed a meta-analysis of randomized controlled trials (RCTs) to better understand the efficacy and safety of MT in treating BAO compared to medical management (MM). Methods PubMed and EMBASE were searched to identify RCTs that directly compared the safety and efficacy of MT versus MM for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Our study showed that the proportion of young Chinese LVO patients who achieved a favorable functional outcome at 3 months after EVT was 42.5% (48/113), which is lower than the 61% in previous studies ( 6 ), although it was mainly about anterior circulation LVO. Our study’s findings were in line with a meta-analysis on posterior circulation EVT, in which the rate of favorable functional outcome was 45.1% ( 26 ), but similar to those on anterior circulation, which revealed that 56% of patients aged 18 to 49 had a favorable outcome ( 13 ). In our study, an increase in the NIHSS score at admission was associated with a lower probability of functional independence at 90 days.…”
Section: Discussionsupporting
confidence: 88%
“…Our study showed that the proportion of young Chinese LVO patients who achieved a favorable functional outcome at 3 months after EVT was 42.5% (48/113), which is lower than the 61% in previous studies ( 6 ), although it was mainly about anterior circulation LVO. Our study’s findings were in line with a meta-analysis on posterior circulation EVT, in which the rate of favorable functional outcome was 45.1% ( 26 ), but similar to those on anterior circulation, which revealed that 56% of patients aged 18 to 49 had a favorable outcome ( 13 ). In our study, an increase in the NIHSS score at admission was associated with a lower probability of functional independence at 90 days.…”
Section: Discussionsupporting
confidence: 88%